Gender and etiological features of modern salmonellosis = Гендерні та етіологічні особливості сучасного сальмонельозу = Гендерные и этиологические особенности современного сальмонеллеза - Chemych, Oksana Mykolaivna; Chemych, Mykola Dmytrovich; Moroz, Larysa Vasylivna (Journal of Education, Health and Sport, 2016)
Chemych O. M., Chemych M. D., Moroz L. V. Gender and etiological features of modern salmonellosis = Гендерні та етіологічні особливості сучасного сальмонельозу = Гендерные и этиологические особенности современного сальмонеллеза Journal of Education, Health and Sport. 2016;6(10):455-470. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164430 http://ojs.ukw.edu.pl/index.php/johs/article/view/3975 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. УДК: 616.9:579.842.14]-07:613.2.099 GENDER AND ETIOLOGICAL FEATURES OF MODERN SALMONELLOSIS Oksana Mykolaivna Chemych1, Mykola Dmytrovich Chemych1, Larysa Vasylivna Moroz2 1Sumy State University, 2, Rymskogo-Korsakova St., Sumy, 40007, Ukraine 2National Pirogov Memorial Medical University, Pirogov str., 56, Vinnytsya, 21018, Ukraine chemychoksana@gmail.com Summary The main clinical and epidemiologic features of modern salmonellosis in acute disease period were analyzed. The studied integrative indices of endogenous intoxication in groups indicate disturbances in the immune system, such as the prevalence of humoral and depression of cellular components of immune system, development of endogenous intoxication due to body autointoxication by destruction of own cells and by influence of bacterial endo- and exotoxins, evident inflammatory reaction. In the acute phase reactions of delayed type prevail over hypersensitivity of immediate type that causes to launching allergic mechanisms on the background of intoxication. Keywords: salmonellosis, clinical picture, integral indicators, integrative indicators, endogenous intoxication. ГЕНДЕРНІ ТА ЕТІОЛОГІЧНІ ОСОБЛИВОСТІ СУЧАСНОГО САЛЬМОНЕЛЬОЗУ Оксана Миколаївна Чемич1, Микола Дмитрович Чемич1, Лариса Василівна Мороз2 1Сумський державний університет, вул. Римського-Корсакова, 2, Суми, 40007, Україна 2Вінницький Національний медичний університет імені М. І. Пирогова, вул. Пирогова, 56, Вінниця, 21018, Україна Резюме Проаналізовано основні клінічні та епідеміологічні ознаки сучасного сальмонельозу в гострий період захворювання. Дослідженні інтегративні показники ендогенної інтоксикації у групах вказують на порушення в імунній системі, а саме превалювання гуморальної і пригнічення клітинної ланок імунітету, розвиток ендогенної інтоксикації внаслідок автоінтоксикації організму при деструкції власних клітин та при дії бактеріальних ендо- та екзотоксинів, виразну запальну реакцію. У гострому періоді спостерігається переважання реакцій уповільненого типу над гіперчутливістю негайного типу, що призводить до запуску алергічних механізмів на тлі інтоксикації. Ключові слова: сальмонельоз, клініка, інтегральні показники, інтегративні показники, ендогенна інтоксикація. ГЕНДЕРНЫЕ И ЭТИОЛОГИЧЕСКИЕ ОСОБЕННОСТИ СОВРЕМЕННОГО САЛЬМОНЕЛЛЕЗА Оксана Николаевна Чемич1, Николай Ддмитриевич Чемич1, Лариса Василиевна Мороз2 1Сумский государственный университет, 2Винницкий Национальный медицинский университет имени Н. И. Пирогова Резюме Проведен анализ основных клинических и эпидемиологических особенностей течения сальмонеллеза в острый период заболевания и выявлены гематологические изменения. Исследованные интегративные показатели эндогенной интоксикации в группах указывают на нарушения в иммунной системе, а именно превалирование гуморального и угнетение клеточного звеньев иммунитета, развитие эндогенной интоксикации вследствие аутоинтоксикации организма при деструкции собственных клеток и при действии бактериальных эндо- и экзотоксинов, выраженную воспалительную реакцию. В остром периоде наблюдается преобладание реакций замедленного типа над гиперчувствительностью немедленного типа, что приводит к запуску аллергических механизмов на фоне интоксикации. Ключевые слова: сальмонеллез, клиника, интегральные показатели, интегративные показатели, эндогенная интоксикация.